2022
DOI: 10.3389/fpls.2022.1034215
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated editing of double loci of BnFAD2 increased the seed oleic acid content of rapeseed (Brassica napus L.)

Abstract: Seed oleic acid is an important quality trait sought in rapeseed breeding programs. Many methods exist to increase seed oleic acid content, such as the CRISPR/Cas9-mediated genome editing system, yet there is no report on seed oleic acid content improvement via this system’s precise editing of the double loci of BnFAD2. Here, a precise CRISPR/Cas9-mediated genome editing of the encoded double loci (A5 and C5) of BnFAD2 was established. The results demonstrated high efficiency of regeneration and transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The PUFA content of seeds is mainly reduced by knocking out FAD genes (Jiang et al, 2017;Morineau et al, 2017;Okuzaki et al, 2018;Huang et al, 2020;Jarvis et al, 2021;Lee et al, 2021;Liu et al, 2022;Shi et al, 2022). Another study successfully decreased the PUFA content by knocking out CIPK9 genes (Wang et al, 2023).…”
Section: Decreased Amounts Of Pufa Can Negatively Affect the Health O...mentioning
confidence: 99%
See 1 more Smart Citation
“…The PUFA content of seeds is mainly reduced by knocking out FAD genes (Jiang et al, 2017;Morineau et al, 2017;Okuzaki et al, 2018;Huang et al, 2020;Jarvis et al, 2021;Lee et al, 2021;Liu et al, 2022;Shi et al, 2022). Another study successfully decreased the PUFA content by knocking out CIPK9 genes (Wang et al, 2023).…”
Section: Decreased Amounts Of Pufa Can Negatively Affect the Health O...mentioning
confidence: 99%
“…For example, oleic acid contents were elevated by knocking out FAD genes (Jiang et al, 2017;Morineau et al, 2017;Okuzaki et al, 2018;Huang et al, 2020;Jarvis et al, 2021;Lee et al, 2021;Liu et al, 2022;Shi et al, 2022).…”
Section: Increasing Amounts Of Oil and Unsaturated Fatty Acids Can Ne...mentioning
confidence: 99%
“…It was discovered that the impact of various mutation types at BnFAD2 alleles on oleic acid levels varied, indicating a potential for fatty acid level manipulation by precise mutation at specific region of a gene ( Huang et al., 2020 ). A recent study on BnFAD2 showed that the CRISPR/Cas9-mediated genome editing of the BnFAD2 ’s double loci (A5 and C5) can precisely edit the targeted genes, increasing the seed’s oleic acid content to a much greater extent than can a single locus-editing technique ( Liu H. et al., 2022 ). Recent findings also reveal that induced mutations in the BnFAD2 genes by CRISPR/Cas9-mediated editing has produce high oleic acid germplasm from the CY2 cultivar ( Shi et al., 2022 ).…”
Section: Fatty Acid Desaturasementioning
confidence: 99%
“… 64 Thlaspi arvense (pennycress) FAD2 , ROD ( reduced oleate desaturase ) Fad2 or fad2 fae1 could double oleic acid contents 65 Arachis hypogea (peanut) FAD2 Seed-specific down regulation of gene led to increased oleic acid content 66 Oryza sativa (rice) OsFAD2–1 Expression of Os FAD2–1 was disrupted which doubled oleic acid contents 67 Brassica napus (rapeseed) fad2_Aa Increase in high oleic acid contents 68 BnaFAD2 Oleic acid contents increased from 65% to 80%. Mutation in BnaFAD2 in A5 genome caused more significant fatty acid profile changes 69 BnFAD2 and BnFAE1 Increase oleic acid (70–80%) with decreased erucic acid 70 BnFAD2 Poor agronomic performance but high oleic acid content while oil content remain constant 71 Glycine max (soybean) GmFAD2 Oleic acid 80% with corresponding decrease in linoleic acid to 1.3% 72 Oleic acid content increased 11% to 40–50% in fad2-1a and fad2-1b mutants, and to 85% in the fad2-1a/fad2 73 Arachis hypogea (peanut) ahFAD2A High oleic acid content 74 Elaeis guineensis (oil palm) EgFAD2 and EgPAT High oleic acid and stearic acid palm oil …”
Section: High Oleic Acid Genetic Stocksmentioning
confidence: 99%